Preparation method of gradient CNT electric heating coating
The gradient CNT electrothermal coating addresses the agglomeration issue by optimizing CNT content and structure, enhancing adhesion and heat transfer for effective anti-icing/de-icing on UAVs.
Patent Information
- Application Number
- CN202410656273.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-24
- Publication Date
- 2024-12-31
AI Technical Summary
Existing electrothermal coatings for unmanned aerial vehicles (UAVs) face issues with agglomeration of carbon nanotubes, leading to decreased adhesion between the coating and the carbon fiber composite substrate, compromising the mechanical properties and stability of the anti-/de-icing system.
A gradient CNT electrothermal coating is prepared by sequentially spraying CNT@polyurethane coatings with varying CNT contents from low to high, using copper foil tape as electrodes, and applying a polyurethane emulsion to create an insulating layer, ensuring adhesion and efficient heat transfer.
The gradient design enhances adhesion and mechanical properties while providing efficient heat accumulation and directional heat transfer, supporting a low-energy consumption/high-efficiency anti-icing/de-icing system for UAVs.
Smart Images

Figure CN119233454A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of unmanned aerial vehicle surface anti-icing / de-icing, and in particular to a method for preparing a gradient CNT electrothermal coating. Background Art
[0002] In recent years, with the rapid development of drone technology, a series of application scenarios have been developed, such as film and television aerial photography, meteorological detection, and geographic surveying and mapping, providing solid support for the development of my country's low-altitude economy. However, under harsh climatic conditions, the surface of drones is prone to ice formation, threatening their flight safety. At the same time, small and medium-sized drones do not have turbine engines to provide air heat for deicing, and mechanical deicing methods will change their aerodynamic shape. Therefore, it has become a top priority to build a lightweight and efficient anti- / deicing system on their surface.
[0003] Carbon fiber composite materials have been widely used in UAV shells due to their advantages such as light weight, high strength and high rigidity. Therefore, solving the problem of ice accumulation on the surface of carbon fiber composite materials can effectively realize the anti-icing / de-icing of UAVs. Electrothermal coatings are considered to be an effective material for solving the problem of ice accumulation on the surface of UAVs due to their own advantages such as light weight, simple preparation process and easy maintenance. However, as the mass fraction of conductive filler carbon nanotubes (CNTs) in conductive coatings increases, although their electrical / electrothermal properties are improved, the agglomeration characteristics of carbon nanotubes themselves will cause the adhesion between the coating and the composite substrate to decrease, which is not conducive to the long-term and stable service of the electrothermal coating. Based on this, the present invention proposes a method for preparing a gradient CNT electrothermal coating, in order to take into account both the mechanical properties and electrothermal properties of the electrothermal coating, and provide a new idea for the construction of UAV anti-icing / de-icing systems. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a gradient CNT electrothermal coating.
[0005] The present invention is achieved through the following technical solutions:
[0006] The present invention relates to a method for preparing a gradient CNT electrothermal coating, comprising the following steps:
[0007] Step 1, polishing the carbon fiber composite material plate with 240 mesh, 400 mesh, and 800 mesh sandpaper in sequence, placing it in a culture dish filled with anhydrous ethanol, washing it in an ultrasonic cleaning machine, and drying it to obtain a pretreated substrate;
[0008] Step 2, respectively spraying CNT@polyurethane mixed conductive coatings with carbon nanotube contents of 6%, 9% and 12% on the carbon fiber composite substrate and curing them to obtain a gradient CNT electrothermal coating;
[0009] Step 3, attaching copper foil tape to both ends of the gradient CNT electric heating coating, and after being completely attached, it acts as the electric heating layer electrode;
[0010] Step 4, uniformly dispersing the polyurethane emulsion in anhydrous ethanol and spraying it on the surface of the gradient electric heating layer with copper foil electrodes, and after curing, constructing an insulating layer on the surface of the electric heating layer to obtain a gradient CNT electric heating coating.
[0011] Preferably, in step 1, the carbon fiber composite material plate has a size of 100 mm×100 mm×1 mm.
[0012] Preferably, in step 1, the ultrasonic cleaning time is 1 hour, and the drying time is 1 hour.
[0013] Preferably, in step 2, the curing temperature is 80° C. and the curing time is 1 hour.
[0014] Preferably, in step 2, the CNT@polyurethane hybrid conductive coating is prepared by the following method:
[0015] 1) 0.06 g, 0.09 g and 0.12 g of CNT were added to 30 g of anhydrous ethanol respectively, stirred evenly and placed in an ultrasonic cleaning machine for 15 min to obtain a CNT suspension;
[0016] 2) 10 g of PU emulsion was added to the CNT suspensions with different contents, and magnetic stirring was performed for 1 h to ensure that the solutions were evenly mixed, thereby preparing CNT@polyurethane hybrid coatings with CNT contents of 6%, 9% and 12%, respectively.
[0017] Preferably, in step 2, the spraying pressure is 6 bar.
[0018] Preferably, in step 3, the size of the copper foil tape is 100 mm×10 mm×0.06 mm.
[0019] Preferably, in step 4, the thickness of the gradient CNT electrothermal coating is 150 μm-250 μm.
[0020] The principle of the invention is as follows: by doping carbon nanotubes with excellent conductivity into polyurethane, the content of carbon nanotube filler is regulated to prepare CNT@polyurethane conductive coatings with different CNT contents, and a simple spraying process is used to spray the coatings with carbon nanotube contents from small to large in sequence and evenly on the surface of carbon fiber composite materials and solidify them, and copper foil tape is pasted on the surface of the gradient CNT electric heating coating to serve as an electrode, and on this basis, polyurethane emulsion is sprayed and solidified to construct an insulating layer.
[0021] The present invention has the following advantages:
[0022] (1) The present invention adopts a gradient design, whereby the electrothermal coating with the lowest CNT content is used as the bottom layer, thereby increasing the adhesion between the coating and the carbon fiber composite material substrate; the coating with a medium CNT content is used as the intermediate transition layer; and the coating with a high CNT content is used as the top layer, thereby achieving efficient electrothermal capacity.
[0023] (2) The present invention constructs electrodes on the surface of an electrothermal coating with a CNT content of 12%, thereby inducing heat accumulation in the gradient coating and the coating surface, thereby achieving a certain degree of directional heat transfer function, and providing a basis for the construction of a low-energy consumption / high-efficiency anti-icing / de-icing system for unmanned aerial vehicles.
[0024] (3) The present invention prepares an insulating coating on the outermost surface of the gradient coating, which not only reduces the roughness of the gradient CNT electrothermal coating, but also helps to improve the anti-icing / de-icing performance of the coating; it also effectively improves the safety of the coating during anti-icing / de-icing work, laying the foundation for its commercial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the structure of the gradient CNT electrothermal coating prepared in Example 2 of the present invention;
[0026] Figure 2 is the relationship between the resistivity of the electrothermal coating and the CNT content;
[0027] Figure 3 This is a cross-sectional microscopic morphology of the gradient CNT electrothermal coating prepared in Example 2 of the present invention;
[0028] Figure 4 The temperature rise curves of Example 2 and Example 3 under the same 8V voltage condition at room temperature are shown;
[0029] Figure 5 The temperature rise curves of the gradient electrothermal coating prepared in Example 2 when an 8V voltage is applied in different environments; wherein, (a) is a temperature rise curve of the gradient electrothermal coating prepared in Example 2 of the present application when an 8V voltage is applied in a low temperature environment; (b) is a temperature rise curve of the gradient electrothermal coating prepared in Example 2 of the present application when an 8V voltage is applied in an icing wind tunnel at -10°C. DETAILED DESCRIPTION
[0030] The present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments are only further descriptions of the present invention, but the protection scope of the present invention is not limited to the following embodiments.
[0031] Example 1
[0032] This embodiment relates to a method for preparing a gradient CNT electrothermal coating, comprising the following steps:
[0033] S1. The carbon fiber composite material plate was polished with 400-mesh sandpaper and placed in a culture dish containing anhydrous ethanol, and then placed in an ultrasonic cleaner for cleaning and drying to obtain a pretreated substrate;
[0034] S2. CNT@polyurethane mixed conductive coatings with carbon nanotube contents of 6%, 9% and 12% were sprayed uniformly on the carbon fiber composite substrate and cured to obtain a gradient CNT electrothermal coating;
[0035] S3. Attach the copper foil tape to both ends of the gradient CNT electrothermal coating, and after being fully attached, it acts as an electrode of the electrothermal layer;
[0036] S4. The polyurethane emulsion is evenly dispersed in anhydrous ethanol and sprayed on the surface of the gradient electric heating layer with copper foil electrodes. After curing, an insulating layer is constructed on the surface of the electric heating layer.
[0037] Step S1 may also include:
[0038] S11. The carbon fiber composite material substrate is polished with 240 mesh, 400 mesh and 800 mesh sandpaper in sequence;
[0039] S12. The polished composite substrate is placed in anhydrous ethanol for ultrasonic cleaning for 1 h;
[0040] S13. After cleaning, the substrate is placed in an 80°C constant temperature oven for 1 hour to dry.
[0041] Step S2 may also include:
[0042] S21. 0.06 g, 0.09 g and 0.12 g of CNT were added to 30 g of anhydrous ethanol, stirred evenly and placed in an ultrasonic cleaner for 15 min to obtain a CNT suspension;
[0043] S22. 10 g of PU emulsion was added to the CNT suspension with different contents, and magnetic stirring was performed for 1 h to ensure that the solution was evenly mixed to prepare CNT@polyurethane hybrid coatings with CNT contents of 6%, 9% and 12% respectively;
[0044] S23. Under a pressure of 6 bar, the conductive coatings with increasing CNT contents are uniformly sprayed on the treated carbon fiber composite substrate in sequence;
[0045] S24. Place the sprayed sample in a constant temperature oven at 80°C for curing for 1 hour to obtain a gradient CNT electrothermal coating.
[0046] After microscopic scanning of the interface, it was found that in some embodiments, see Figure 2The microscopic morphology of the cross-section of the electric heating layer shows that the thickness of the electric heating layer of the gradient CNT electric heating coating is about 200μm, which can fully meet the principle of lightweight design of UAVs.
[0047] Step S4 may also include:
[0048] S41. The polyurethane emulsion is dispersed in anhydrous ethanol and magnetically stirred at room temperature for 30 min to achieve complete dispersion to obtain a polyurethane dispersion, wherein the mass ratio of the polyurethane emulsion to the anhydrous ethanol is 1:2;
[0049] S42. The polyurethane dispersion was evenly sprayed on the surface of the gradient CNT electrothermal coating with a copper foil tape at a pressure of 6 bar;
[0050] S43. Place the sample in an oven at 80°C for curing for 1 hour to prepare an insulating layer on the coating surface.
[0051] After the gradient electric heating coating is prepared, the coating surface is inspected: ① The coating appearance should not have defects such as cracks and voids; ② A voltage of 28V is applied to both ends of the coating, and the peak temperature at room temperature is ≥100℃; ③ A voltage of 28V is applied to both ends of the coating, and the peak temperature in the icing wind tunnel (ambient temperature is -10℃, wind speed is 40m / s) is ≥0℃.
[0052] Example 2
[0053] This embodiment relates to a method for preparing a gradient CNT electrothermal coating, comprising the following steps:
[0054] The carbon fiber composite substrate was polished with 240-mesh, 400-mesh and 800-mesh sandpaper in turn, the polished carbon fiber composite plate was ultrasonically cleaned in anhydrous ethanol for 1 hour, and the substrate after cleaning was placed in a constant temperature oven at 80°C for 1 hour to complete the pretreatment of the carbon fiber composite substrate.
[0055] 0.06g, 0.09g and 0.12g CNT were added to 30g anhydrous ethanol respectively, stirred evenly and placed in an ultrasonic cleaner for 15min to obtain a CNT suspension. 10g PU emulsion was added to the CNT suspensions with different contents, and magnetic stirring was performed for 1h to ensure that the solution was evenly mixed to prepare CNT@polyurethane hybrid coatings with CNT contents of 6%, 9% and 12%, respectively. Under a pressure of 6 bar, the conductive coatings with CNT contents from small to large were uniformly sprayed on the treated carbon fiber composite substrate in sequence, and the sprayed samples were placed in a constant temperature oven at 80°C for curing for 1h to obtain a gradient CNT electrothermal coating. Figure 1 , Figure 2 , Figure 3 shown; from Figure 2It can be seen that as the CNT content gradually increases, its resistivity shows a trend of first decreasing and then increasing. When the CNT content is 12%, its resistivity drops to the minimum. However, as the CNT filler content increases, the adhesion between the coating resins will be reduced, thereby reducing the mechanical properties of the coating. Therefore, the present invention selects three conductive coatings with CNT contents from low to high to prepare a gradient electrothermal coating, which overcomes the disadvantage that a single coating cannot take into account both mechanical properties and high-efficiency electrothermal properties.
[0056] from Figure 3 It can be seen that there is no obvious dividing line between the gradient electrothermal coatings, indicating that the coatings with different CNT contents have excellent interface connection performance, which will significantly enhance their mechanical properties.
[0057] The temperature rise of the gradient CNT electrothermal coating prepared in Example 2 was changed by applying 8V voltage under different conditions. Figure 5 shown.
[0058] Copper foil tape is pasted on the surface of the prepared gradient CNT electrothermal coating to serve as an electrode.
[0059] The polyurethane emulsion was dispersed in anhydrous ethanol and magnetically stirred at room temperature for 30 minutes to achieve complete dispersion, thereby obtaining a polyurethane dispersion, wherein the mass ratio of the polyurethane emulsion to anhydrous ethanol was 1:2; the polyurethane dispersion was evenly sprayed on the surface of the gradient CNT electrothermal coating with a copper foil tape at a pressure of 6 bar; the sample was placed in an oven at 80°C for curing for 1 hour to prepare an insulating layer on the coating surface.
[0060] Example 3
[0061] This embodiment relates to a method for preparing a composite electric heating unit. The remaining steps are the same as those in Embodiment 2, except for the pasting position of the copper foil tape. This embodiment includes the following steps:
[0062] The carbon fiber composite substrate was polished with 240-mesh, 400-mesh and 800-mesh sandpaper in turn, the polished carbon fiber composite plate was ultrasonically cleaned in anhydrous ethanol for 1 hour, and the substrate after cleaning was placed in a constant temperature oven at 80°C for 1 hour to complete the pretreatment of the carbon fiber composite substrate.
[0063] Copper foil tape is pasted on the surface of the pretreated carbon fiber composite material substrate to serve as an electrode.
[0064] 0.06g, 0.09g and 0.12g CNT were added to 30g anhydrous ethanol respectively, stirred evenly and placed in an ultrasonic cleaner for 15min to obtain a CNT suspension. 10g PU emulsion was added to the CNT suspension with different contents, and magnetic stirring was performed for 1h to ensure that the solution was mixed evenly to prepare CNT@polyurethane mixed coatings with CNT contents of 6%, 9% and 12%, respectively. Under a pressure of 6bar, the conductive coatings with CNT contents from small to large were uniformly sprayed on the treated carbon fiber composite substrate in sequence, and the sprayed samples were placed in a constant temperature oven at 80℃ for curing for 1h to obtain a gradient CNT electrothermal coating.
[0065] The polyurethane emulsion was dispersed in anhydrous ethanol and magnetically stirred at room temperature for 30 minutes to achieve complete dispersion, thereby obtaining a polyurethane dispersion, wherein the mass ratio of the polyurethane emulsion to anhydrous ethanol was 1:2; the polyurethane dispersion was evenly sprayed on the surface of the gradient CNT electrothermal coating with a copper foil tape at a pressure of 6 bar; the sample was placed in an oven at 80°C for curing for 1 hour to prepare an insulating layer on the coating surface.
[0066] The temperature rise of the gradient CNT electrothermal coatings prepared in Example 2 and Example 3 under the same 8V voltage condition at room temperature is shown in FIG. Figure 4 As shown. Figure 4 It can be seen that compared with placing the copper foil electrode at the bottom, placing it on a coating with better surface conductivity, the temperature difference is nearly 70°C after powering on for three minutes under the same conditions. This shows that through reasonable distribution of the copper foil electrode positions, gradient coating heat accumulation and the outer surface can be effectively achieved, further improving the coating's electrothermal capacity.
[0067] The present invention constructs electrodes on the surface of an electrothermal coating with a CNT content of 12%, thereby inducing heat accumulation of the gradient coating and the coating surface, thereby achieving a certain degree of directional heat transfer function, and providing a basis for the construction of a low-energy consumption / high-efficiency anti-icing / de-icing system for unmanned aerial vehicles; the present invention prepares an insulating coating on the outermost surface of the gradient coating, which not only reduces the roughness of the gradient CNT electrothermal coating, but also is more conducive to improving the anti-icing / de-icing performance of the coating; it also effectively improves the safety of the coating during anti-icing / de-icing work, laying a foundation for its commercial application.
[0068] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which will not affect the essence of the present invention.
Claims
1. A method for preparing a gradient CNT electrothermal coating, characterized in that: The steps include: Step 1, polishing the carbon fiber composite material plate with 240 mesh, 400 mesh, and 800 mesh sandpaper in sequence, placing it in a culture dish filled with anhydrous ethanol, washing it in an ultrasonic cleaning machine, and drying it to obtain a pretreated substrate; Step 2, respectively spraying CNT@polyurethane mixed conductive coatings with carbon nanotube contents of 6%, 9% and 12% on the carbon fiber composite substrate and curing them to obtain a gradient CNT electrothermal coating; Step 3, attaching copper foil tape to both ends of the gradient CNT electric heating coating, and after being completely attached, it acts as the electric heating layer electrode; Step 4, uniformly dispersing the polyurethane emulsion in anhydrous ethanol and spraying it on the surface of the gradient electric heating layer with copper foil electrodes, and after curing, constructing an insulating layer on the surface of the electric heating layer to obtain a gradient CNT electric heating coating.
2. The method for preparing a gradient CNT electrothermal coating according to claim 1, characterized in that: In step 1, the size of the carbon fiber composite material plate is 100 mm×100 mm×1 mm.
3. The method for preparing a gradient CNT electrothermal coating according to claim 1, characterized in that: In step 1, the ultrasonic cleaning time is 1 hour, and the drying time is 1 hour.
4. The method for preparing a gradient CNT electrothermal coating according to claim 1, characterized in that: In step 2, the curing temperature is 80° C. and the curing time is 1 hour.
5. The method for preparing a gradient CNT electrothermal coating according to claim 1, characterized in that: In step 2, the CNT@polyurethane hybrid conductive coating is prepared by the following method: 1) 0.06 g, 0.09 g and 0.12 g of CNT were added to 30 g of anhydrous ethanol respectively, stirred evenly and placed in an ultrasonic cleaning machine for 15 min to obtain a CNT suspension; 2) 10 g of PU emulsion was added to the CNT suspensions with different contents, and magnetic stirring was performed for 1 h to ensure that the solutions were evenly mixed, thereby preparing CNT@polyurethane hybrid coatings with CNT contents of 6%, 9% and 12%, respectively.
6. The method for preparing a gradient CNT electrothermal coating according to claim 1, characterized in that: In step 2, the spraying pressure is 6 bar.
7. The method for preparing a gradient CNT electrothermal coating according to claim 1, characterized in that: In step 3, the size of the copper foil tape is 100 mm×10 mm×0.06 mm.
8. The method for preparing a gradient CNT electrothermal coating according to claim 1, characterized in that: In step 4, the thickness of the gradient CNT electrothermal coating is 150 μm-250 μm.
